Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

raebaby420

  • 3 years ago

solve for y in the first equation. x + 3y = 6 2x – y = 10

  • This Question is Closed
  1. SamuelAlden917
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    x - 3y + 2x - 7y = - 6 + 10 10y = 3x - 4 y = 0.3x - 0.4 x - 3(0.3x - 0.4) = - 6 x - 0.9x + 1.2 = - 6 0.1x = - 7.2 x = - 72 y = 0.3(- 72) - 0.4 y = - 21.6 - .4 y = - 22 Answer: x = - 72, y = - 22

  2. SamuelAlden917
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Help?

  3. SamuelAlden917
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    ?

  4. raebaby420
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Sorry, stepped away

  5. raebaby420
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    My answer choices are ..

  6. raebaby420
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    1/3x+2 -1/3x+6 -x+2 -1/3+2

  7. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy